Age of Mammuthus trogontherii from Kostolac, Serbia, and the entry of megaherbivores into Europe during the Late Matuyama climate revolution. Issue 3 (November 2015) - Muttoni, Giovanni; Scardia, Giancarlo; Dimitrijević, Vesna; Kent, Dennis V.; Monesi, Edoardo; Mrdjić, Nemanja; Korać, Miomir
Abstract : At the Drmno open-pit coal mine near Kostolac in Serbia, a nearly complete skeleton of Mammuthus trogontherii (nicknamed Vika) was discovered in a fluvial deposit overlain by a loess–paleosol sequence where a second paleontological level named Nosak with remains of M. trogontherii was found. We studied the magnetostratigraphy of the Kostolac sedimentary sequence and found that the Vika layer dates to 0.8 Ma, shortly before the Brunhes–Matuyama boundary. In addition, according to our age model and previously reported optically stimulated luminescence and electron spin resonance dates, the Nosak fossils have an estimated age of 0.19 Ma and lived during the earliest part of Marine Isotope Stage 6. It appears therefore that at Kostolac, M. trogontherii is preserved both at its earliest occurrence at 0.8 Ma and close to its latest occurrence at 0.19 Ma, and may well have been present in between, albeit not yet found. We speculate that megaherbivores such as M. trogontherii entered Europe along a conjunct Danube–Po River migration conduit connecting western Asia-Levant with central-southern Europe where vast and exploitable ecosystems, particularly suited for steppe- or savanna-adapted megaherbivores from Asia and Africa, developed during the late early Pleistocene climate revolution at around 0.8 Ma.